Urolithin A attenuates osteoclast differentiation and compensates for ovariectomy-induced bone loss in mice by inhibiting PI3K/AKT/mTOR signaling pathway - Wenyun Zhou; Weijun Zhou; Zibin Zhou; Yonghao Bi; Zhigao Zhou; Shaozhe Chen; Zihong Lin; Jiajie Ye; Gang Xie; Wenjie Liu; Dantao Xie; Zhen Lian; et al. (Elsevier, 2024)
Backgrounds and purposes: Osteoporosis (OP) is a debilitating illness distinguished by a reduction in bone density and microstructure, which leads to fragility, fracture risk, and increased mortality, particularly in the elderly and postmenopausal women. Growing evidence suggests that various plant derivatives could be a potential therapy for osteoporosis. Ellagic acid is a phenolic found naturally in extracts from plants such as pomegranate, blackberry and berry. In earlier research, ellagic acid (EA) was reported to have certain benefits on osteoporosis, however, EA was limited by its weak bioactivity. Urolithin A (UA), an ellagic acid metabolite present in the intestinal bacteria, which had a greater bioavailability. However, its therapeutic effects and mechanisms in osteoporosis remain to be explored. Study design: In this work, we explored about how UA affected the molecular processes of osteoclasts differentiation in vitro. We also performed the ovariectomy-induced osteoporotic mice model in order to evaluate how UA impacted the bone loss of osteoporosis. Methods: 1. TRAP staining analysis to examine the impact of UA on osteoclast differentiation. 2. RT-PCR for evaluating UA's impact on the expression of genes relevant to osteoclasts. Bone resorption experiment and scan by electron microscope in order to determine the impact of UA on osteoclast function. 3.Using western blotting, investigate the impact of UA on the osteoclast differentiation-related signaling pathway. 4. Developed an osteoporosis mouse model for evaluating the preventative impact of UA on bone loss after an ovariectomy. Results: 1. UA reduced osteoclast development in a dosage manner without cytotoxicity. 2. UA suppresses osteoclast-related gene expression as well as the function of osteoclast bone resorption. 3. UA regulates osteoclast development by decreasing PI3K/AKT/mTOR signaling pathway phosphorylation as well as Nfatc1 transcription and translation. 4. Animal study demonstrated that UA reduced bone loss in ovariectomy-induced osteoporotic mice. Conclusion: UA reduced the development and bone resorption function of osteoclast, was shown as inhibiting expression of osteoclast-associated specific genes as well as the PI3K/AKT/mTOR signaling pathway and decreasing Nfatc1 expression. In vivo, UA prevented bone loss in ovariectomy-induced osteoporotic mice. Finally, UA shown tremendous promise in the prevention and treatment of osteoporosis.